Contribuição para a concepção de aplicações no paradigma orientado a notificações (PON) sob o viés de padrões - Ronszcka, Adriano Francisco (2012)
The original materialization of Notification Oriented Paradigm (NOP) previously implemented in the C++ programming language allowed the creation of applications under the domain of this paradigm. Although these contributions to the paradigm, the development of NOP applications still has a low level of maturity and a certain degree of difficulty. Such difficulties arise essentially from the new form of structuring programs, in which such applications follow a notification flow, which differs from the conventional programming. Moreover, so far, only a few applications have been developed, with relatively small scope, which does not contribute effectively to the consolidation of the paradigm, and particularly for learning through an effective set of examples. Henceforth, firstly, the general structure of the framework has been reread and reintroduced under the bias of design patterns, even as there were contributions in its implementation. Subsequently, the main goal of this paper is to guide the development of applications based on NOP in a more streamlined and efficient manner, using the advances mentioned here. This was achieved particularly by the presentation of technical software implementations aimed to this paradigm and its infrastructure, which pursues a manner to conceive more purist implementations, involving issues such as reducing the use of multiparadigms implementations, simplifying the development, ensuring determinism, and so far. In general, the new features for conceiving applications based on the NOP Framework made easier and better its use.